1976
DOI: 10.2134/agronj1976.00021962006800020063x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Electronic Foliometer to Measure Leaf Area in Corn and Soybeans1

Abstract: Known areas were measured with an electronic foliometer to determine the errors involved with this instrument. Good agreement between measured and known areas was found and there was high accuracy and precision for both the conveyor belt and sheath method. Tests were made comparing the foliometer, a planimeter, and maximum length times maximum width (LW) for soybeans and comparing foliometer and LW for corn. There was close agreement between planimeter and foliometer measurements for soybeans (r = 0.99). The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Weekly measurements were made of the number of leaf collars and leaf tips to record the phenological development on 10 plants in each monolith. Measurements were made of the length and maximum width of each new fully emerged leaf to estimate leaf area by multiplying length  width  0.67 using the procedure described by Hatfield et al (1976). These measurements continued until all leaves emerged.…”
Section: Methodsmentioning
confidence: 99%
“…Weekly measurements were made of the number of leaf collars and leaf tips to record the phenological development on 10 plants in each monolith. Measurements were made of the length and maximum width of each new fully emerged leaf to estimate leaf area by multiplying length  width  0.67 using the procedure described by Hatfield et al (1976). These measurements continued until all leaves emerged.…”
Section: Methodsmentioning
confidence: 99%
“…Weekly measurements were made of the number of leaf collars and leaf tips to record the phenological development on 10 plants in each monolith. Measurements were made of the length and maximum width of each new fully emerged leaf to estimate leaf area by multiplying length × width × 0.67 using the procedure described by Hatfield et al (1976). These measurements continued until all leaves emerged.…”
Section: Methodsmentioning
confidence: 99%
“…Rice samples for LAI measurement were collected at approximately 10-day intervals during growing seasons from 2010 to 2012 (Table 1) LAI was measured with LI-3100C Area Meter (Li-Cor Inc.), where the projected image of a leaf sample traveling under a fluorescent light source is reflected by a system of mirrors to a solid-state scanning camera. Hatfield et al (1976) reported that measurement error with this type of area meter is generally less than 2%.…”
Section: Methodsmentioning
confidence: 95%